Exchange rates and firm export performance in South Africa - Lawrence Edwards; Ayanda Hlatshwayo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper uses detailed firm transaction data on manufactured exports to analyse the dilution of the real exchange rate-export relationship in South Africa over the period 2010 to 2014. Our empirical results show that firms that are larger, have higher export shares in destination markets, and import are more likely to raise the domestic currency price of their exports in response to a depreciation, and consequently display weaker export quantity responses. The exchange rate responsiveness is also weaker for exporters of resource-based manufactured products and those that export outside Africa. South African manufactured exports are highly concentrated among a few large firms that rely heavily on imported intermediate inputs and predominantly export resource-based products. Consequently, these results provide an explanation for the low aggregate export response to the sustained depreciation over the period 2010 to 2014.
Keywords: F14; F31; F32; 330; exchange rate; pass-through; exports; South Africa